Taiwan: Patent term extension in Taiwan - LIU, Kung-chung (Institutional Knowledge at Singapore Management University, 2016)
Unlike some European jurisdictions, Taiwan does not have a supplementary protection certificate that grants a patentee an independent, sui generis IP right. Rather, under Taiwan Patent Act, a patent term extension is available only on two occasions. Firstly, when a patentee of an invention of pharmaceuticals (excluding veterinary drugs), agrochemicals, or the manufacturing processes thereof, obtains the market authorization by another authority from the central government required by law for the exploitation of the patented invention after the patent was granted by the Taiwan IP Office (TIPO).442 Secondly, Article 66 of Taiwan Patent Act allows a patentee of an invention unable to practice his/her patent due to war between Republic of China (ROC more commonly known as Taiwan) and other foreign countries to extend his/her patent term once for a period of between 5 to 10 years. However, patentees from the foreign county that is in war with Taiwan are not eligible for patent term extension. In patent practice the patent term extension regime is rarely used in Taiwan. Unless otherwise specified, patent term extension mentioned hereinafter refers only to extension for pharmaceutical and agrochemicals patents and the manufacturing processes thereof.